Multidetector (64+) Computed Tomography Angiography of the Lower Limb in Symptomatic Peripheral Arterial Disease: Assessment of Image Quality and Accuracy in a Tertiary Care Setting. Issue 2 (March 2017) - Lim, Jeremy C.; Ranatunga, Dinesh; Owen, Andrew; Spelman, Tim; Galea, Michael; Chuen, Jason; Lim, Ruth P.
Abstract : Objective: The aim of this study was to evaluate image quality and accuracy of 64+ detector multidetector computed tomography angiography (MDCTA) for hemodynamically significant (≥50%) stenosis in patients with symptomatic peripheral arterial disease (PAD) using digital subtraction angiography as the reference standard. Methods: This is a retrospective study of 29 patients with PAD (19 men, 10 women) who underwent lower limb MDCTA (64- or 80-detector) and digital subtraction angiography. Image quality and accuracy of MDCTA for hemodynamically significant stenosis were assessed in the infrarenal aorta and 15 lower extremity segments. Results: Four hundred fifty-three segments were adequately visualized at both modalities. Multidetector CTA had 84.8% sensitivity, 87.7% specificity, and 86.3% accuracy for significant stenosis. Accuracy was decreased in the calf when compromising arterial wall calcifications were present versus absent (55.9% vs 82.4%, P < 0.0001). Conclusions: 64+ MDCTA is accurate in patients with symptomatic PAD. However, diagnostic accuracy in below-knee vessels remains relatively poorer. Alternative imaging modalities should be considered where below-knee disease is suspected.